2022
DOI: 10.3390/tomography8010014
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Artery to Pulmonary Artery Shunt Mimicking Acute Pulmonary Embolism, Unmasked by a Multimodality Imaging Approach

Abstract: In this report, we describe the functional imaging findings of systemic artery to pulmonary artery shunt in V/Q SPECT CT imaging. A 63-year-old man with small-cell lung cancer underwent CT pulmonary angiography (CTPA) for suspected acute pulmonary embolism (PE). The CTPA showed an isolated segmental filling defect in the right lower lobe, which was initially interpreted as positive for PE but was actually the consequence of a systemic artery to pulmonary artery shunt due to the recruitment of the bronchial art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…It also leads to inadvertent administration of anticoagulants in a patient with haemoptysis, thus further worsening the situation. Dissaux et al 1 reported SAPA shunt as a rare cause of filling defects in the pulmonary arteries on CTPA. Toupchiani et al 2 reported the case of a middle-aged woman whose CT pulmonary angiogram showed a pulmonary arterial filling defect, which was subsequently found to be false positive due to an underlying SAPA shunt.…”
Section: Descriptionmentioning
confidence: 99%
“…It also leads to inadvertent administration of anticoagulants in a patient with haemoptysis, thus further worsening the situation. Dissaux et al 1 reported SAPA shunt as a rare cause of filling defects in the pulmonary arteries on CTPA. Toupchiani et al 2 reported the case of a middle-aged woman whose CT pulmonary angiogram showed a pulmonary arterial filling defect, which was subsequently found to be false positive due to an underlying SAPA shunt.…”
Section: Descriptionmentioning
confidence: 99%